All-solid-state battery, preparation method thereof and electric equipment

By introducing functional nanoparticles of three-dimensional porous structures and permanent dipole dielectric materials into all-solid-state batteries and using polymer electrolytes, the problem of large interface impedance of the battery is solved, significantly improving the performance indicators of the battery.

CN119725683APending Publication Date: 2025-03-28GAC AION NEW ENERGY AUTOMOBILE CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411917538.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Due to the large interface impedance of existing all-solid-state batteries, they lead to poor first-time charge and discharge specific capacity, first-time Coulomb efficiency, rate performance and cycle performance.

Method used

By introducing functional nanoparticles of three-dimensional porous structures and permanent dipole dielectric materials into the sulfide solid electrolyte, and introducing polymer electrolytes into the battery, an interface structure with face-to-face contact is formed to reduce the interface impedance.

Benefits of technology

It effectively reduces the interface impedance between the sulfide solid electrolyte and the electrode plate, and improves the first charge and discharge specific capacity, first Coulomb efficiency, rate performance and cycle performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725683A_ABST
    Figure CN119725683A_ABST
Patent Text Reader

Abstract

The invention provides an all-solid-state battery, a preparation method thereof and electric equipment, and belongs to the technical field of all-solid-state battery manufacturing. The all-solid-state battery comprises a positive plate, a sulfide solid-state electrolyte and a negative plate which are sequentially laminated and distributed, the sulfide solid-state electrolyte comprises a sulfide solid-state electrolyte matrix with a three-dimensional porous structure and functional nanoparticles which are positioned on the positive electrode side of the sulfide solid-state electrolyte matrix and are distributed in a dotted manner; the functional nanoparticles are made of a permanent dipole dielectric material, and polymer electrolytes are arranged in the three-dimensional porous structure, on the surfaces of the functional nanoparticles, between the positive plate and the sulfide solid electrolyte and between the negative plate and the sulfide solid electrolyte; according to the all-solid-state battery, the interface impedance between the sulfide solid electrolyte and the pole piece can be effectively reduced, so that the battery has relatively excellent first charge-discharge specific capacity, first coulombic efficiency, rate capability and cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of all-solid-state battery manufacturing, and more specifically, to an all-solid-state battery and a preparation method and electrical equipment thereof. Background Art

[0002] In the prior art, all-solid-state batteries have become a potential preferred solution for the next generation of power batteries due to their advantages such as high energy density and high safety. However, current solid-state batteries have a problem of large interface impedance on the positive electrode side. Specifically, on the one hand, driven by the chemical potential difference, lithium ions easily migrate from the solid electrolyte side to the positive electrode side, so that a lithium-deficient layer is formed on the electrolyte side and a lithium-rich layer is formed on the positive electrode side, resulting in the formation of a space charge layer, thereby forming a high lithium ion migration energy barrier, so that the solid-state battery has a large interface impedance at the interface between the battery positive electrode and the solid electrolyte; on the other hand, the current sulfide all-solid-state battery pole piece and the sulfide solid electrolyte are usually in point contact, which makes the interface between the solid electrolyte and the positive and negative electrode sheets usually have a large interface impedance, and as the solid-state battery undergoes charge and discharge cycles, the volume of the positive and negative electrode materials will usually change, so that the interface contact effect between the solid electrolyte and the positive and negative electrode sheets will be further deteriorated. Due to the above two problems, the existing all-solid-state batteries have a large interface impedance between the sulfide solid electrolyte and the electrode, which in turn leads to poor first charge and discharge specific capacity, first coulomb efficiency, rate performance and cycle performance of the all-solid-state batteries. Summary of the invention

[0003] The purpose of the present application is to provide an all-solid-state battery and its preparation method and electrical equipment. The all-solid-state battery can effectively reduce the interface impedance between the sulfide solid electrolyte and the electrode, so that the battery has a relatively excellent first charge and discharge specific capacity, first coulomb efficiency, rate performance and cycle performance.

[0004] The embodiment of the present application is implemented as follows:

[0005] In a first aspect, an embodiment of the present application provides an all-solid-state battery, comprising a positive electrode sheet, a sulfide solid electrolyte and a negative electrode sheet stacked in sequence, wherein the sulfide solid electrolyte comprises a sulfide solid electrolyte matrix with a three-dimensional porous structure, and functional nanoparticles distributed in a point shape and located on the positive electrode side of the sulfide solid electrolyte matrix, the material of the functional nanoparticles comprises a permanent dipole dielectric material, and a polymer electrolyte is present in the three-dimensional porous structure, on the surface of the functional nanoparticles, between the positive electrode sheet and the sulfide solid electrolyte, and between the negative electrode sheet and the sulfide solid electrolyte.

[0006] In the above technical solution, on the one hand, one side of the sulfide solid electrolyte matrix is ​​loaded with functional nanoparticles distributed in a point shape, and the material of the functional nanoparticles includes a permanent dipole dielectric material. The permanent dipole dielectric material can generate a permanent reverse electric dipole under the electric field effect of the space charge layer (the permanent dipole dielectric is composed of positively charged atomic nuclei and negatively charged electrons. These charges are tightly bound by the forces within the atoms or molecules. When the dielectric is placed in an external electric field, the internal charges will be rearranged, resulting in a macroscopic change in charge distribution. This phenomenon is called polarization), thereby balancing the difference in lithium ion concentration at the interface between the positive electrode and the solid electrolyte, so that after the functional particles with such dielectric properties are arranged on the sulfide solid electrolyte side, the adverse effects of the formation of the space charge layer on lithium ion transmission can be reduced (i.e., a high lithium ion migration energy barrier is formed, which leads to an increase in the lithium ion migration impedance at the interface), so as to solve the problem of high interface impedance caused by the formation of the space charge layer due to the difference in lithium ion concentration. On the other hand, by introducing polymer electrolytes capable of transmitting lithium ions into all-solid-state batteries, specifically, polymer electrolytes are present in the three-dimensional porous structure, on the surface of functional nanoparticles, between the positive electrode and the sulfide solid electrolyte, and between the negative electrode and the sulfide solid electrolyte; this structural design can not only adjust the point-to-point contact between the solid electrolyte and the electrode to surface-to-surface contact, thereby effectively reducing the interface impedance between the solid electrolyte and the positive and negative electrode sheets; at the same time, a complete lithium ion transmission channel can be formed between the positive and negative electrodes, thereby enhancing the transmission effect of lithium ions; in addition, the presence of polymer electrolytes on the surface of functional nanoparticles helps to improve the ion transmission performance in this area, and helps the functional nanoparticles to better reduce the adverse effects of the formation of the space charge layer on lithium ion transmission. Through the combined effect of the two aspects, the interface impedance between the sulfide solid electrolyte and the electrode can be effectively reduced, so that the battery has a relatively excellent first charge and discharge specific capacity, first coulomb efficiency, rate performance and cycle performance.

[0007] In some optional embodiments, the permanent dipole dielectric material is selected from at least one of BaTiO3 and SrTiO3.

[0008] In the above technical solution, the permanent dipole dielectric material made of the above material has the advantage of a higher dielectric constant, which can more effectively balance the difference in lithium ion concentration at the interface between the positive electrode and the solid electrolyte, thereby more effectively reducing the lithium ion migration impedance of the battery at the positive electrode interface.

[0009] In some optional embodiments, the mass percentage of the functional nanoparticles in the sulfide solid electrolyte is 0.05-0.3%.

[0010] In the above technical solution, the mass proportion of functional nanoparticles in the sulfide solid electrolyte is limited to a specific range, wherein the lower limit of the mass percentage can better reduce the impedance at the positive electrode interface, and the upper limit of the mass percentage can make the sulfide solid electrolyte have a more suitable ion transport performance, so that the sulfide solid electrolyte can effectively reduce the interface impedance on the positive electrode side while having a more suitable ion transport performance.

[0011] In some optional embodiments, the particle size of the functional nanoparticles is 10 to 100 nm.

[0012] In the above technical scheme, the particle size of the functional nanoparticles is limited to a specific range so that the functional nanoparticles have a more suitable particle size, wherein the lower limit of the particle size can better reduce the impedance at the positive electrode interface, and the upper limit of the particle size can make the sulfide solid electrolyte have a more suitable ion transport performance, so that the sulfide solid electrolyte can effectively reduce the interface impedance on the positive electrode side while having a more suitable ion transport performance.

[0013] In some optional embodiments, the polymer electrolyte includes 66-83% of polymer macromolecules and 17-34% of lithium salts, calculated by mass percentage.

[0014] In the above technical solution, the polymer electrolyte contains a specific mass percentage of polymer macromolecules and lithium salt, so that the polymer electrolyte has a more suitable flexibility, thereby enabling the polymer electrolyte to have more sufficient contact between adjacent interfaces, so as to better reduce the interface impedance; at the same time, the appropriate mass percentage of lithium salt can also make the polymer electrolyte have a better lithium ion transmission effect.

[0015] In some optional embodiments, the monomer of the polymer macromolecule is selected from at least one of ethylene glycol methyl ether acrylate, ethylene glycol diglycidyl ether and ethylene glycol diacrylate.

[0016] In the above technical solution, the applicable types of monomers of the polymer macromolecule are relatively rich, and can be adaptively adjusted according to actual needs, thereby providing more feasible implementation plans.

[0017] In some optional embodiments, the lithium salt is selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium trifluoromethanesulfonate, lithium bistrifluoromethanesulfonyl imide, lithium bisfluorosulfonyl imide, lithium difluorooxalatoborate and lithium bisoxalate borate.

[0018] In the above technical solutions, the applicable types of lithium salts are relatively rich, and can be adaptively adjusted according to actual needs, thereby providing more feasible implementation plans.

[0019] In a second aspect, an embodiment of the present application provides a method for preparing an all-solid-state battery as provided in an embodiment of the first aspect, comprising the following steps:

[0020] A positive electrode sheet and a negative electrode sheet are provided; a sulfide solid electrolyte matrix is ​​provided; functional nanoparticles are dispersed in a non-polar organic solvent to form a mixed solution; the mixed solution is applied to the sulfide solid electrolyte matrix by using an electrostatic spray deposition technique so that the functional nanoparticles are loaded on one side of the surface of the sulfide solid electrolyte matrix to obtain a sulfide solid electrolyte; the positive electrode sheet, the sulfide solid electrolyte and the negative electrode sheet are stacked in sequence, wherein the functional nanoparticles are located on the positive electrode side of the sulfide solid electrolyte matrix to obtain a bare battery cell; the bare battery cell is then placed in a battery casing and a precursor solution of a polymer electrolyte is injected into the casing under vacuum conditions; a heat treatment is then performed so that the precursor solution is in situ solidified to form a polymer electrolyte to obtain an all-solid-state battery.

[0021] In the above technical scheme, the preparation according to the above method can prepare an all-solid-state battery that can effectively reduce the interface impedance between the sulfide solid electrolyte and the pole piece; on the one hand, the use of non-polar organic solvent is to prevent the sulfide in the solid electrolyte matrix from reacting with the solvent during the preparation process, so that the structure of the solid electrolyte matrix is ​​destroyed and the ion transmission performance thereof is reduced; the electrostatic spray deposition technology is used because the process is easy to implement and batch, and at the same time, the sulfide solid electrolyte prepared by this method also has the advantage of a relatively uniform distribution of functional nanoparticles, so that the positive electrode and the solid electrolyte can be more effectively balanced. On the other hand, the precursor solution is injected under vacuum conditions and then the polymer electrolyte is grown in situ after heat treatment, so that the precursor solution can fully infiltrate the electrode and fully fill the porous channels in the sulfide solid electrolyte, so that the formed polymer electrolyte has better continuity and thus has better lithium ion transport performance. At the same time, it can also better adjust the point contact between the solid electrolyte and the electrode to surface contact, thereby effectively reducing the interface impedance between the solid electrolyte and the positive and negative electrode sheets.

[0022] In some optional embodiments, the organic solvent is selected from at least one of n-dodecane, n-heptane and n-hexane.

[0023] In the above technical solution, the use of the above-mentioned types of organic solvents can better disperse the functional nanoparticles, and at the same time, it is not easy to cause side reactions with sulfides.

[0024] In some optional embodiments, the solid content of the mixed solution is 0.1-2%.

[0025] In the above technical solution, the solid content in the mixed solution is limited to a specific range, which helps to better disperse the functional nanoparticles so that the functional nanoparticles can be more evenly distributed on the surface of the sulfide solid electrolyte matrix after spraying.

[0026] In some optional embodiments, the step of dispersing the functional nanoparticles in a non-polar organic solvent is performed under ultrasonic conditions, wherein the ultrasonic power is 20 to 50 KHz and the ultrasonic time is 0.5 to 3 h.

[0027] In the above technical solution, ultrasound-assisted dispersion is used to make the difficult-to-disperse functional nanoparticles more evenly dispersed in the organic solvent, so that the functional nanoparticles can be more evenly distributed on the surface of the sulfide solid electrolyte matrix after spraying.

[0028] In some optional embodiments, in the step of electrostatic spray deposition, at least one of the following conditions A to E is met:

[0029] The distance from nozzle A to the surface of the sulfide solid electrolyte substrate is 5 to 20 cm.

[0030] B voltage is 10~50KV.

[0031] C spraying rate is 1~5mL / h.

[0032] D Spraying time is 0.25 to 2 hours.

[0033] The temperature of the E sulfide solid electrolyte matrix is ​​210-250°C.

[0034] In the above technical scheme, the distance, voltage, spraying rate, spraying time and substrate temperature in the electrostatic spraying deposition step are respectively limited within specific ranges, which can conveniently and efficiently deposit the functional nanoparticles on the surface of the sulfide solid electrolyte substrate. At the same time, the functional nanoparticles can be more evenly distributed on the surface of the sulfide solid electrolyte substrate after spraying.

[0035] In a third aspect, an embodiment of the present application provides an electrical device, including an all-solid-state battery provided in the embodiment of the first aspect. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0037] Figure 1A schematic diagram of the structure inside a shell of an all-solid-state battery provided in an embodiment of the present application;

[0038] Figure 2 A schematic diagram of the structure of a sulfide solid electrolyte provided in an embodiment of the present application;

[0039] Figure 3 A process flow chart of a method for preparing an all-solid-state battery provided in an embodiment of the present application.

[0040] Icon: 10-all-solid-state battery; 100-positive electrode; 200-sulfide solid electrolyte; 210-sulfide solid electrolyte matrix; 220-functional nanoparticles; 300-negative electrode; 400-polymer electrolyte. DETAILED DESCRIPTION

[0041] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all the embodiments. The components of the embodiments of the present application described and shown in the drawings here can be arranged and designed in various different configurations.

[0042] Therefore, the following detailed description of the embodiments of the present application provided in the accompanying drawings is not intended to limit the scope of the present application for which protection is sought, but merely represents selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.

[0043] It should be noted that similar reference numerals and letters represent similar items in the following drawings, so once an item is defined in one drawing, it does not need to be further defined and explained in subsequent drawings. In the description of this application, it should be noted that the terms "first", "second", etc. are only used to distinguish the description and cannot be understood as indicating or implying relative importance.

[0044] In the description of this application, it should also be noted that, unless otherwise clearly specified and limited, the terms "set", "install", "connect", and "connect" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a direct connection, or an indirect connection through an intermediate medium, or it can be the internal communication of two elements. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.

[0045] The following is a detailed description of a sulfide solid electrolyte and its preparation method, an all-solid-state battery, and an electrical device of the present application.

[0046] See also Figure 1 and Figure 2 In the first aspect, the embodiment of the present application provides an all-solid-state battery 10, comprising a positive electrode sheet 100, a sulfide solid electrolyte 200 and a negative electrode sheet 300 which are stacked in sequence, wherein the sulfide solid electrolyte 200 comprises a sulfide solid electrolyte matrix 210 with a three-dimensional porous structure, and functional nanoparticles 220 which are distributed in a point shape and are located on the positive electrode side of the sulfide solid electrolyte matrix 210, wherein the material of the functional nanoparticles 220 comprises a permanent dipole dielectric material, and a polymer electrolyte 400 is provided in the three-dimensional porous structure, on the surface of the functional nanoparticles 220, between the positive electrode sheet 100 and the sulfide solid electrolyte 200, and between the negative electrode sheet 300 and the sulfide solid electrolyte 200.

[0047] In the present application, on the one hand, one side of the sulfide solid electrolyte matrix 210 is loaded with functional nanoparticles 220 distributed in a point shape, and the material of the functional nanoparticles 220 includes a permanent dipole dielectric material, which can generate a permanent reverse electric dipole under the electric field effect of the space charge layer (the permanent dipole dielectric is composed of positively charged atomic nuclei and negatively charged electrons. These charges are tightly bound by the forces within the atoms or molecules. When the dielectric is placed in an external electric field, the charges inside it will be rearranged, resulting in a macroscopic change in charge distribution. This phenomenon is called polarization), thereby balancing the difference in lithium ion concentration at the interface between the positive electrode and the solid electrolyte, so that after the functional particles with such dielectric properties are arranged on the side of the sulfide solid electrolyte 200, the adverse effects of the formation of the space charge layer on the lithium ion transport can be reduced (i.e., a high lithium ion migration energy barrier is formed, which leads to an increase in the lithium ion migration impedance at the interface), so as to solve the problem of high interface impedance caused by the formation of the space charge layer due to the difference in lithium ion concentration. On the other hand, by introducing a polymer electrolyte 400 capable of transporting lithium ions into the all-solid-state battery 10, specifically, the polymer electrolyte 400 is present in the three-dimensional porous structure, on the surface of the functional nanoparticles 220, between the positive electrode 100 and the sulfide solid electrolyte 200, and between the negative electrode 300 and the sulfide solid electrolyte 200; this structural design can not only adjust the point contact between the solid electrolyte and the electrode to surface contact, thereby effectively reducing the interface impedance between the solid electrolyte and the positive and negative electrode sheets 300; at the same time, it can also form a complete lithium ion transmission channel between the positive electrode sheet 100 and the negative electrode sheet 300, thereby enhancing the lithium ion transmission effect; in addition, the presence of the polymer electrolyte 400 on the surface of the functional nanoparticles 220 helps to improve the ion transmission performance in this area, and helps the functional nanoparticles 220 to better reduce the adverse effects of the formation of the space charge layer on lithium ion transmission. Through the combined effect of these two aspects, the interface impedance between the sulfide solid electrolyte 200 and the electrode can be effectively reduced, so that the battery has a relatively excellent first charge and discharge specific capacity, first coulomb efficiency, rate performance and cycle performance.

[0048] It should be noted that the type of permanent dipole dielectric material is not limited and can be adaptively adjusted according to actual needs.

[0049] As an example, the permanent dipole dielectric material is selected from at least one of BaTiO 3 and SrTiO 3 .

[0050] In this embodiment, the permanent dipole dielectric material of the above material has the advantage of a higher dielectric constant, which can more effectively balance the difference in lithium ion concentration at the interface between the positive electrode and the solid electrolyte, thereby more effectively reducing the lithium ion migration impedance of the battery at the positive electrode interface.

[0051] It is understandable that if the mass proportion of the functional nanoparticles 220 is relatively small, it will be difficult to effectively balance the difference in lithium ion concentration between the positive electrode side and the solid electrolyte layer, and it will be difficult to effectively reduce the interfacial impedance; if the mass proportion of the functional nanoparticles 220 is relatively large, since the particles are not ion conductive, the lithium ion transport performance of the sulfide solid electrolyte 200 will be reduced. Based on this, the mass proportion of the functional nanoparticles 220 in the sulfide solid electrolyte 200 can be optimized.

[0052] As an example, in the sulfide solid electrolyte 200, the mass percentage of the functional nanoparticles 220 is 0.05-0.3%, for example but not limited to any one of 0.05%, 0.1%, 0.15%, 0.2%, 0.25% and 0.3% or a range between any two of the mass percentages.

[0053] In this embodiment, the mass percentage of the functional nanoparticles 220 in the sulfide solid electrolyte 200 is limited to a specific range, wherein the lower limit of the mass percentage can better reduce the impedance at the positive electrode interface, and the upper limit of the mass percentage can make the sulfide solid electrolyte 200 have a more suitable ion transmission performance. By limiting the mass percentage of the functional nanoparticles 220 in the sulfide solid electrolyte 200 to a specific range, the sulfide solid electrolyte 200 can effectively reduce the interface impedance on the positive electrode side while having a more suitable ion transmission performance.

[0054] As an example, the particle size of the functional nanoparticles 220 is 10 to 100 nm, for example but not limited to any point value among 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm and 100 nm or a range value between any two thereof.

[0055] In this embodiment, the particle size of the functional nanoparticles 220 is limited to a specific range so that the functional nanoparticles 220 have a more suitable particle size, wherein the lower limit setting of the particle size can better reduce the impedance at the positive electrode interface, and the upper limit of the particle size can enable the sulfide solid electrolyte 200 to have a more suitable ion transmission performance, so that the sulfide solid electrolyte 200 can effectively reduce the interface impedance on the positive electrode side while having a more suitable ion transmission performance.

[0056] It should be noted that the form of the polymer electrolyte 400 is not limited, for example, the material itself is an ion-conducting material, or it can be a mixture of a non-ion-conducting polymer macromolecule and a lithium salt.

[0057] As an example, the polymer electrolyte 400 includes, by mass percentage, 66-83% (for example, but not limited to, any one of 66%, 70%, 75%, 80% and 83% or a range between any two) of polymer macromolecules and 17-34% (for example, but not limited to, any one of 17%, 20%, 25%, 30% and 34% or a range between any two) of lithium salt.

[0058] In this embodiment, the polymer electrolyte 400 contains polymer macromolecules and lithium salts in specific mass percentages, so that the polymer electrolyte 400 has a more suitable flexibility, thereby enabling the polymer electrolyte 400 to have more sufficient contact between adjacent interfaces, so as to better reduce the interface impedance; at the same time, the lithium salt with a suitable mass percentage can also make the polymer electrolyte 400 have a more excellent lithium ion transmission effect.

[0059] As an example, the monomer of the polymer is selected from at least one of ethylene glycol methyl ether acrylate, ethylene glycol diglycidyl ether and ethylene glycol diacrylate.

[0060] In this embodiment, the applicable types of monomers of the polymer macromolecule are relatively abundant and can be adaptively adjusted according to actual needs, thereby providing more feasible implementation plans.

[0061] As an example, the lithium salt is selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium trifluoromethanesulfonate, lithium bistrifluoromethanesulfonyl imide, lithium bisfluorosulfonyl imide, lithium difluorooxalatoborate and lithium bisoxalateborate.

[0062] In this embodiment, the applicable types of lithium salts are relatively rich and can be adaptively adjusted according to actual needs, thereby providing more feasible implementation plans.

[0063] It should be noted that the specific structures of the positive electrode sheet 100 and the negative electrode sheet 300 are not limited and can be configured according to conventional selections in the art.

[0064] As an example, in the negative electrode sheet 300, the negative electrode current collector is selected from pure metal copper foil or a metal and polymer composite foil; the negative electrode active material is selected from at least one of lithium metal, silicon, silicon carbon, silicon oxygen, graphite and hard carbon; the conductive agent is selected from at least one of nano-carbon fiber, vapor-grown carbon fiber, SuperP, acetylene black, KS6, CNT and graphene; the binder is selected from at least one of SBR, ABR, BR, PAA, SEBS and PIB.

[0065] As an example, in the positive electrode sheet 100, the positive electrode current collector is selected from pure metal Al foil or a foil composite of metal and polymer; the positive electrode active material is selected from at least one of lithium cobalt oxide, lithium iron phosphate, lithium manganese oxide, lithium nickel oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide and lithium-rich manganese-based materials; the conductive agent is selected from at least one of vapor-grown carbon fiber, SuperP, acetylene black, KS6, CNT and graphene; the binder is selected from at least one of PTFE, SEBS and PIB.

[0066] It should be noted that any structure or functional unit not specifically described in the all-solid-state battery 10 may be configured according to conventional options in the art.

[0067] In a second aspect, an embodiment of the present application provides a method for preparing an all-solid-state battery as provided in an embodiment of the first aspect, comprising the following steps:

[0068] A positive electrode sheet and a negative electrode sheet are provided; a sulfide solid electrolyte matrix is ​​provided; functional nanoparticles are dispersed in a non-polar organic solvent to form a mixed solution; the mixed solution is applied to the sulfide solid electrolyte matrix by using an electrostatic spray deposition technique so that the functional nanoparticles are loaded on one side of the surface of the sulfide solid electrolyte matrix to obtain a sulfide solid electrolyte; the positive electrode sheet, the sulfide solid electrolyte and the negative electrode sheet are stacked in sequence, wherein the functional nanoparticles are located on the positive electrode side of the sulfide solid electrolyte matrix to obtain a bare battery cell; the bare battery cell is then placed in a battery casing and a precursor solution of a polymer electrolyte is injected into the casing under vacuum conditions; a heat treatment is then performed so that the precursor solution is in situ solidified to form a polymer electrolyte to obtain an all-solid-state battery.

[0069] In the present application, the preparation according to the above method can prepare an all-solid-state battery that can effectively reduce the interface impedance between the sulfide solid electrolyte and the pole piece; on the one hand, the use of non-polar organic solvent is to prevent the sulfide in the solid electrolyte matrix from reacting with the solvent during the preparation process, so that the structure of the solid electrolyte matrix is ​​destroyed and its ion transmission performance is reduced; the electrostatic spray deposition technology is used because the process is easy to implement and batch, and at the same time, the sulfide solid electrolyte prepared by this method also has the advantage of a relatively uniform distribution of functional nanoparticles, so that the positive electrode and the solid electrolyte can be more effectively balanced. The difference in lithium ion concentration at the interface can effectively reduce the lithium ion migration impedance of the battery at the positive electrode interface; on the other hand, the precursor solution is injected under vacuum conditions and then heated to obtain an in-situ grown polymer electrolyte, so that the precursor solution can fully infiltrate the electrode and fully fill the porous channels in the sulfide solid electrolyte, so that the formed polymer electrolyte has better continuity and thus has better lithium ion transmission performance. At the same time, it can also better adjust the point contact between the solid electrolyte and the electrode to surface contact, thereby effectively reducing the interface impedance between the solid electrolyte and the positive and negative electrode sheets.

[0070] It should be noted that the preparation method of the sulfide solid electrolyte matrix with a three-dimensional porous structure can be prepared according to conventional processes in the art.

[0071] As an example, the preparation method of the sulfide solid electrolyte matrix includes the following steps:

[0072] The sulfide electrolyte powder, pore former and binder are mixed by ball milling, wherein the mass ratio of the three is 1:(0.2-5):(0.02-0.1), the rotation speed of the ball milling is 100-600rpm, and the ball milling time is 0.5-12h; the mixture obtained by ball milling is hot pressed into a self-supporting film, wherein the hot pressing temperature is 25°C-120°C, and the film thickness is 30-100μm; then the self-supporting film is heated to vaporize the pore former and leave pores inside the self-supporting film, wherein the heating temperature is 210-250°C, and the heating time is 2-5h, to obtain a sulfide solid electrolyte matrix with a three-dimensional porous structure.

[0073] It should be noted that the type of sulfide electrolyte powder is not limited, for example, it can be Li2S-P2S5, Li6PS5X or Li 10 GeP2S 12 At least one of, wherein X is Cl, Br or I.

[0074] As an example, the organic solvent is selected from at least one of n-dodecane, n-heptane and n-hexane.

[0075] In this embodiment, the use of the above-mentioned types of organic solvents can better disperse the functional nanoparticles and is not prone to side reactions with sulfides.

[0076] As an example, the solid content of the mixed solution is 0.1-2%, for example but not limited to any one of 0.1%, 0.5%, 1%, 1.5% and 2% or a range between any two of the solid content.

[0077] In this embodiment, limiting the solid content in the mixed solution within a specific range helps to better disperse the functional nanoparticles so that the functional nanoparticles can be more evenly distributed on the surface of the sulfide solid electrolyte matrix after spraying.

[0078] As an example, the step of dispersing the functional nanoparticles in a non-polar organic solvent is carried out under ultrasonic conditions, wherein the ultrasonic power is 20 to 50 KHz, for example but not limited to the ultrasonic power being any point value among 20 KHz, 30 KHz, 40 KHz and 50 KHz or a range value between any two thereof; the ultrasonic time is 0.5 to 3 h, for example but not limited to the time being any point value among 0.5 h, 1 h, 2 h and 3 h or a range value between any two thereof.

[0079] In this embodiment, ultrasound-assisted dispersion is used to make the difficult-to-disperse functional nanoparticles more uniformly dispersed in the organic solvent, thereby making the functional nanoparticles more uniformly distributed on the surface of the sulfide solid electrolyte matrix after spraying.

[0080] As an example, in the step of electrostatic spray deposition, at least one of the following conditions A to E is satisfied:

[0081] The distance from nozzle A to the surface of the sulfide solid electrolyte matrix is ​​5 to 20 cm, for example but not limited to any one of 5 cm, 10 cm, 15 cm and 20 cm or a range between any two of them.

[0082] The voltage B is 10-50 KV, for example but not limited to any one of 10 KV, 20 KV, 30 KV, 40 KV and 50 KV or a range between any two of them.

[0083] C spraying rate is 1-5 mL / h, for example but not limited to the spraying rate of any one of 1 mL / h, 2 mL / h, 3 mL / h, 4 mL / h and 5 mL / h or a range between any two thereof.

[0084] D The spraying time is 0.25 to 2 hours, for example but not limited to any one of 0.25 hours, 0.5 hours, 1 hour, 1.5 hours and 2 hours, or a range between any two of them.

[0085] The temperature of the E sulfide solid electrolyte matrix is ​​210-250°C, for example but not limited to any one of 210°C, 220°C, 230°C, 240°C and 250°C or a range between any two of them.

[0086] It should be noted that the sulfide solid electrolyte matrix has a relatively high temperature in order to volatilize the organic solvent quickly and completely.

[0087] In this embodiment, the distance, voltage, spraying rate, spraying time and substrate temperature in the electrostatic spraying deposition step are respectively limited within specific ranges, so that the functional nanoparticles can be conveniently and efficiently deposited on the surface of the sulfide solid electrolyte substrate. At the same time, the functional nanoparticles can be more evenly distributed on the surface of the sulfide solid electrolyte substrate after spraying.

[0088] It should be noted that any process or step not specifically described or limited in the preparation of the sulfide solid electrolyte may be arranged according to conventional selection in the art.

[0089] As an example, the preparation method of the polymer electrolyte includes the following steps:

[0090] The positive electrode sheet, the sulfide solid electrolyte and the negative electrode sheet are stacked in sequence to obtain a bare battery cell; the bare battery cell is placed in a battery shell and the inside of the shell is evacuated so that the vacuum degree of the injection port is -70 to -100 Kpa, and then the precursor solution of the polymer electrolyte is injected into the shell and left to stand for 2 to 12 hours so that the precursor solution fully infiltrates the positive electrode sheet, the sulfide solid electrolyte and the negative electrode sheet, and then sealed; the entire battery after sealing is placed in an oven for heat treatment so that the precursor solution undergoes an in-situ polymerization reaction to form a transition layer. Among them, the precursor solution is a mixed solution formed by mixing polymer high molecular monomers, initiators and lithium salts, and the mass ratio of polymer high molecular monomers to initiators in the precursor solution is 1: (0.01 to 0.1); the heat treatment temperature is 60°C and the time is 6 to 16 hours.

[0091] As an example, the initiator is selected from at least one of azobisisobutyronitrile, benzoyl peroxide and ammonium persulfate.

[0092] It should be noted that any process or step not specifically described in the all-solid-state battery may be performed according to conventional processes in the art.

[0093] As an example, the process flow chart of the preparation method of all-solid-state battery can be found in Figure 3 .

[0094] In a third aspect, an embodiment of the present application provides an electrical device, including an all-solid-state battery provided in the embodiment of the first aspect.

[0095] It should be noted that there is no limitation on the specific type of electrical equipment, and it can be adaptively adjusted according to actual needs.

[0096] The features and performance of the present application are further described in detail below in conjunction with the embodiments.

[0097] Example 1

[0098] The present invention provides a method for preparing an all-solid-state battery, comprising the following steps:

[0099] S1 pole piece preparation:

[0100] According to the mass percentage, 97% positive electrode active material (lithium iron phosphate), 1.5% conductive agent (acetylene black), and 1.5% binder (PTFE) were dissolved in NMP to obtain a positive electrode slurry with a solid content of 60%. The positive electrode slurry was then coated on Al foil and dried to obtain a positive electrode sheet.

[0101] According to the mass percentage, 97% of negative electrode active material (graphite), 1.5% of conductive agent (acetylene black), and 1.5% of binder (SEBS) were dissolved in water to obtain a negative electrode slurry with a solid content of 50%. The negative electrode slurry was then coated on a Cu foil and dried to obtain a negative electrode sheet.

[0102] Preparation of S2 sulfide solid electrolyte:

[0103] Take 100g of sulfide solid electrolyte powder (Li6PS5Cl, 50g of selenium disulfide (pore-forming agent), ball-mill at 400rpm for 6h, then add 5g of PTFE (binder) and continue ball-milling at 600rpm for 8h, hot-press the mixed slurry obtained by ball milling at 100℃ into a 50μm self-supporting film, and then heat-treat the self-supporting film at 220℃ for 3h to obtain a sulfide solid electrolyte matrix. 5g of 100nm BaTiO3 is dispersed in n-dodecane (a non-polar organic solvent), and ultrasonically treated for 1h at an ultrasonic power of 20KHz to form a mixed solution with a solid content of 2%; the mixed solution is applied to a sulfide solid electrolyte matrix by electrostatic spray deposition technology, wherein, in the electrostatic spray deposition step, the distance from the nozzle to the surface of the sulfide solid electrolyte matrix is ​​5cm, the voltage is 40KV, the spraying rate is 3mL / h, the spraying time is 0.25h, and the temperature of the sulfide solid electrolyte matrix is ​​220°C, so that the functional nanoparticles are loaded on one side of the surface of the sulfide solid electrolyte matrix, wherein the loading amount is 0.15%, and a sulfide solid electrolyte is obtained.

[0104] S3 forms a transition layer in situ to obtain an all-solid-state battery:

[0105] The positive electrode sheet, the sulfide solid electrolyte and the negative electrode sheet are stacked in sequence, wherein the functional nanoparticles are located on the side facing the positive electrode sheet, to obtain a bare battery cell; the bare battery cell is placed in a battery shell and the inside of the shell is evacuated so that the vacuum degree of the injection port is -80Kpa, and then the precursor solution of the transition layer is injected into the shell and left to stand for 6 hours, so that the precursor solution fully infiltrates the positive electrode sheet, the sulfide solid electrolyte and the negative electrode sheet, and then sealed; the entire battery after sealing is placed in an oven for heat treatment so that the precursor solution undergoes an in-situ polymerization reaction to form a transition layer; wherein the precursor solution is a mixed solution formed by mixing a polymer macromolecular monomer (ethylene glycol methyl ether acrylate), an initiator (azobisisobutyronitrile) and a lithium salt (lithium hexafluorophosphate), wherein the mass ratio of the polymer macromolecular monomer to the lithium salt is 75:25; the heat treatment temperature is 60°C and the time is 12 hours to obtain an all-solid-state battery with a transition layer.

[0106] Example 2

[0107] The embodiment of the present application provides a method for preparing an all-solid-state battery, which differs from Embodiment 1 only in that the particle size of BaTiO3 is 50 nm.

[0108] Example 3

[0109] The embodiment of the present application provides a method for preparing an all-solid-state battery, which differs from Embodiment 1 only in that the particle size of BaTiO3 is 10 nm.

[0110] Example 4

[0111] The embodiment of the present application provides a method for preparing an all-solid-state battery, which differs from Example 1 only in that: in the electrostatic spray deposition step, the spraying rate is 1 mL / h, the spraying time is 0.25 h, and the temperature of the sulfide solid electrolyte matrix is ​​220°C, so that the functional nanoparticles are loaded on one side surface of the sulfide solid electrolyte matrix, wherein the loading amount is 0.05%, and a sulfide solid electrolyte is obtained.

[0112] Example 5

[0113] The embodiment of the present application provides a method for preparing an all-solid-state battery, which differs from Example 1 only in that: in the electrostatic spray deposition step, the spraying rate is 3 mL / h, the spraying time is 0.5 h, and the temperature of the sulfide solid electrolyte matrix is ​​220°C, so that the functional nanoparticles are loaded on one side surface of the sulfide solid electrolyte matrix, wherein the loading amount is 0.3%, and a sulfide solid electrolyte is obtained.

[0114] Comparative Example 1

[0115] The comparative example of the present application provides a method for preparing an all-solid-state battery, comprising the following steps:

[0116] S1 pole piece preparation:

[0117] According to the mass percentage, 97% positive electrode active material (lithium iron phosphate), 1.5% conductive agent (acetylene black), and 1.5% binder (PTFE) were dissolved in NMP to obtain a positive electrode slurry with a solid content of 60%. The positive electrode slurry was then coated on Al foil and dried to obtain a positive electrode sheet.

[0118] According to the mass percentage, 97% of negative electrode active material (graphite), 1.5% of conductive agent (acetylene black), and 1.5% of binder (SEBS) were dissolved in water to obtain a negative electrode slurry with a solid content of 50%. The negative electrode slurry was then coated on a Cu foil and dried to obtain a negative electrode sheet.

[0119] Preparation of S2 sulfide solid electrolyte:

[0120] Take 100g of sulfide solid electrolyte powder (Li6PS5Cl), then add 5g of PTFE (binder) and continue ball milling at 600rpm for 8h. The mixed slurry obtained by ball milling is hot pressed at 100℃ into a 50μm self-supporting film, namely the sulfide solid electrolyte.

[0121] S3 all-solid-state battery assembly:

[0122] The positive electrode sheet, the sulfide solid electrolyte and the negative electrode sheet are stacked in sequence to obtain a bare battery cell; the bare battery cell is placed in a battery casing and packaged to obtain an all-solid-state battery.

[0123] Comparative Example 2

[0124] The comparative example of the present application provides a method for preparing an all-solid-state battery, which differs from Example 1 only in that n-dodecane does not contain BaTiO3, that is, the sulfide solid electrolyte does not contain functional nanoparticles with point-like distribution.

[0125] Comparative Example 3

[0126] The comparative example of the present application provides a method for preparing an all-solid-state battery, which differs from Example 1 only in that:

[0127] Preparation of S2 sulfide solid electrolyte:

[0128] Take 100g of sulfide solid electrolyte powder (Li6PS5Cl), then add 5g of PTFE (binder) and continue ball milling at a speed of 600rpm for 8h. The mixed slurry obtained by ball milling is hot pressed into a 50μm self-supporting film at 100℃, and then the self-supporting film is heat treated at 220℃ for 3h to obtain a sulfide solid electrolyte matrix. 5 g of 100 nm BaTiO3 was dispersed in n-dodecane (a non-polar organic solvent), and ultrasonically treated at an ultrasonic power of 20 KHz for 1 h to form a mixed solution with a solid content of 2%; the mixed solution was applied to a sulfide solid electrolyte matrix by electrostatic spray deposition technology, wherein, in the electrostatic spray deposition step, the distance from the nozzle to the surface of the sulfide solid electrolyte matrix was 5 cm, the voltage was 40 KV, the spraying rate was 3 mL / h, the spraying time was 0.25 h, and the temperature of the sulfide solid electrolyte matrix was 220°C, so that the functional nanoparticles were loaded on one side of the surface of the sulfide solid electrolyte matrix, wherein the loading amount was 0.15%, and a sulfide solid electrolyte was obtained.

[0129] S3 all-solid-state battery assembly:

[0130] The positive electrode sheet, the sulfide solid electrolyte and the negative electrode sheet are stacked in sequence, wherein the functional nanoparticles are located on the side facing the positive electrode sheet, to obtain a bare battery cell; the bare battery cell is placed in a battery casing and packaged to obtain an all-solid-state battery.

[0131] Comparative Example 4

[0132] The comparative example of the present application provides a method for preparing an all-solid-state battery, which differs from Example 1 only in that BaTiO3 is completely replaced by TiO2.

[0133] Comparative Example 5

[0134] The comparative example of the present application provides a method for preparing an all-solid-state battery, which differs from Example 1 only in that no pore-forming agent is added.

[0135] Comparative Example 6

[0136] The comparative example of the present application provides a method for preparing an all-solid-state battery, which differs from Example 1 only in that the battery casing is not evacuated before liquid injection, that is, the precursor solution is not injected under vacuum conditions, resulting in problems of insufficient wetting and filling.

[0137] Test example

[0138] Electrical performance test of all-solid-state batteries

[0139] Test method:

[0140] The all-solid-state batteries prepared in Examples 1 to 5 and Comparative Examples 1 to 6 were numbered respectively, and then the first charge and discharge specific capacity, first coulombic efficiency, 1C / 0.1C rate performance and capacity retention rate after 200 cycles of each sample were tested, and the results were statistically summarized in Table 2.

[0141] Among them, the test steps for the first charge and discharge specific capacity are as follows:

[0142] At 25°C, the battery is charged to 4.3V at a constant current of 0.1C, then charged at a constant voltage to a current less than or equal to 0.05C, then allowed to stand for 5 minutes, and then discharged to 2.5V at a constant current of 0.1C, then allowed to stand for 5 minutes. This is a charge and discharge cycle. The charging capacity and discharge capacity of this time are respectively recorded as the charging specific capacity and discharge specific capacity of the battery in the first cycle.

[0143] Among them, the test steps for the first coulomb efficiency are as follows:

[0144] At 25°C, the battery is charged to 4.3V at a constant current of 0.1C, then charged at a constant voltage to a current less than or equal to 0.05C, then allowed to stand for 5 minutes, and then discharged to 2.5V at a constant current of 0.1C, then allowed to stand for 5 minutes. This is a charge and discharge cycle. The charging capacity and discharge capacity of this time are respectively recorded as the charging specific capacity and discharge specific capacity of the battery in the first cycle. The ratio of the first discharge specific capacity to the first charging specific capacity is the first coulombic efficiency.

[0145] The test steps for 1C / 0.1C rate performance are as follows:

[0146] First, a charge and discharge cycle is performed at 0.1C, and then a charge and discharge cycle is performed at 1C. The 1C discharge capacity is divided by the discharge capacity at 0.1C to obtain the 1C / 0.1C rate performance.

[0147] The test steps of cycle performance are as follows:

[0148] At 25°C, the battery was charged to 4.3V at a constant current of 1C, then charged at a constant voltage to a current less than or equal to 0.05C, then allowed to stand for 5 minutes, and then discharged to 2.5V at a constant current of 1C, then allowed to stand for 5 minutes. This was a charge and discharge cycle, which was repeated 200 times. The 200th cycle discharge capacity was divided by the first discharge capacity to obtain the 200th cycle capacity retention rate.

[0149] Table 1

[0150]

[0151] Referring to Table 1, it can be seen from the test results of Examples 1 to 5 and Comparative Examples 1 to 3 that when the sulfide solid electrolyte is loaded with functional nanoparticles of a permanent dipole dielectric material on the side close to the positive electrode sheet, and there are polymer electrolytes in the three-dimensional porous structure, on the surface of the functional nanoparticles, between the positive electrode sheet and the sulfide solid electrolyte, and between the negative electrode sheet and the sulfide solid electrolyte, the corresponding all-solid-state battery can effectively reduce the interface impedance between the electrode sheet and the sulfide solid electrolyte, thereby having relatively excellent first charge and discharge specific capacity, first coulomb efficiency, rate performance and cycle performance.

[0152] It can be seen from the test results of Example 1 and Comparative Example 4 that when a specific type of functional nanoparticles is used, compared with functional nanoparticles of other materials, the all-solid-state battery corresponding to the former can effectively reduce the interfacial impedance on the positive electrode side, thereby having a relatively excellent first charge and discharge specific capacity, first coulombic efficiency, rate performance and cycle performance.

[0153] It can be seen from the test results of Example 1 and Comparative Example 5 that when a sulfide solid electrolyte with a three-dimensional porous structure is used and a polymer electrolyte is arranged in the pores and on both sides, compared with using a sulfide solid electrolyte without a three-dimensional porous structure and only arranging polymer electrolytes on both sides thereof, the all-solid-state battery corresponding to the former can effectively reduce the interfacial impedance on the positive electrode side, thereby having a relatively excellent first charge and discharge specific capacity, first coulomb efficiency, rate performance and cycle performance.

[0154] It can be seen from the test results of Example 1 and Comparative Example 6 that the battery shell is evacuated before liquid injection (that is, the precursor solution is injected under vacuum conditions), compared with the case where the battery shell is not evacuated before liquid injection (that is, the precursor solution is not injected under vacuum conditions), the former corresponding all-solid-state battery can effectively reduce the interfacial impedance on the positive electrode side, thereby having a relatively excellent first charge and discharge specific capacity, first coulomb efficiency, rate performance and cycle performance.

[0155] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. An all-solid-state battery, characterized in that: It comprises a positive electrode sheet, a sulfide solid electrolyte and a negative electrode sheet which are stacked in sequence, wherein the sulfide solid electrolyte comprises a sulfide solid electrolyte matrix with a three-dimensional porous structure, and functional nanoparticles which are distributed in a point shape and are located on the positive electrode side of the sulfide solid electrolyte matrix, the material of the functional nanoparticles comprises a permanent dipole dielectric material, and polymer electrolytes are present in the three-dimensional porous structure, on the surface of the functional nanoparticles, between the positive electrode sheet and the sulfide solid electrolyte, and between the negative electrode sheet and the sulfide solid electrolyte.

2. The all-solid-state battery according to claim 1, characterized in that: The permanent dipole dielectric material is selected from at least one of BaTiO3 and SrTiO3.

3. The all-solid-state battery according to claim 2, characterized in that: In the sulfide solid electrolyte, the mass percentage of the functional nanoparticles is 0.05-0.3%.

4. The all-solid-state battery according to claim 3, characterized in that: The particle size of the functional nanoparticles is 10-100 nm.

5. The all-solid-state battery according to any one of claims 1 to 4, characterized in that: According to mass percentage, the polymer electrolyte includes 66-83% of polymer macromolecules and 17-34% of lithium salt.

6. The all-solid-state battery according to claim 5, characterized in that: The monomer of the polymer macromolecule is selected from at least one of ethylene glycol methyl ether acrylate, ethylene glycol diglycidyl ether and ethylene glycol diacrylate.

7. The all-solid-state battery according to claim 5, characterized in that: The lithium salt is selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium trifluoromethanesulfonate, lithium bistrifluoromethanesulfonyl imide, lithium bisfluorosulfonyl imide, lithium difluorooxalatoborate and lithium bisoxalateborate.

8. A method for preparing an all-solid-state battery as claimed in any one of claims 1 to 7, characterized in that: The following steps are involved: Providing the positive electrode sheet and the negative electrode sheet; Providing the sulfide solid electrolyte matrix, dispersing the functional nanoparticles in a non-polar organic solvent to form a mixed solution; applying the mixed solution to the sulfide solid electrolyte matrix by using an electrostatic spray deposition technique so that the functional nanoparticles are loaded on one side surface of the sulfide solid electrolyte matrix, thereby obtaining the sulfide solid electrolyte; The positive electrode sheet, the sulfide solid electrolyte and the negative electrode sheet are stacked in sequence, wherein the functional nanoparticles are located on the positive electrode side of the sulfide solid electrolyte matrix, to obtain a bare battery cell; the bare battery cell is then placed in a battery casing and a precursor solution of the polymer electrolyte is injected into the casing under vacuum conditions; a heat treatment is then performed to allow the precursor solution to solidify in situ to form the polymer electrolyte, to obtain the all-solid-state battery.

9. The preparation method according to claim 8, characterized in that: The organic solvent is selected from at least one of n-dodecane, n-heptane and n-hexane.

10. The preparation method according to claim 8, characterized in that: The solid content of the mixed solution is 0.1-2%.

11. The preparation method according to claim 8, characterized in that: The step of dispersing the functional nanoparticles in a non-polar organic solvent is performed under ultrasonic conditions, wherein the ultrasonic power is 20 to 50 KHz and the ultrasonic time is 0.5 to 3 hours.

12. The preparation method according to any one of claims 8 to 11, characterized in that: In the electrostatic spray deposition step, at least one of the following conditions A to E is met: The distance between nozzle A and the surface of the sulfide solid electrolyte matrix is ​​5 to 20 cm; B voltage is 10~50KV; C spraying rate is 1~5mL / h; D spraying time is 0.25~2h; The temperature of the E sulfide solid electrolyte matrix is ​​210-250°C.

13. An electrical equipment, characterized in that: It comprises the all-solid-state battery as claimed in any one of claims 1 to 7.

Citation Information

Patent Citations

  • Method of manufacturing separator for lithium secondary battery, separator manufactured using said method, and lithium secondary battery including said separator

    CN104040756A

  • High-dielectric composite solid electrolyte, integrated all-solid-state battery and preparation method

    CN118738524A

  • All-solid-state battery

    JP2013062133A

  • Electrode and electrochemical device including the same

    KR1020150049999A